(3GdEM`GdI Edi GdbVGA GdLf`GFj (B:s "(3OQGSI ebGQfI(B" /s - (3eMe`hO QeV`Gf EH`QGgj`es; (3YeQ eMeO SGdes; (3YGOd jMji bQfjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2021)
(3jgOa bGfhf GdYbhHGJ Edi MeGjI GdeUGdM GdGLJeGYjI GdJj jQi GdeTQY GdLfGFj CfgG LOjQI HGdMeGjI, hPdc Yf WQjb JONd GdeTQY dJLQje HYV GdCaYGd hJbQjQ GdYbhHGJ dgG, hMJi jDOj bGfhf GdYbhHGJ gPg GdQSGdI JWdH GdCeQ hLhO GdhSjdI GdJj HebJVGgG JSJWjY GdOhdI hVY GdMeGjI GdLfGFjI ddeUGdM GdGLJeGYjI ehVY GdJfajP, aeLQO Cf JQJcH GdLQjeI jfTC ddeLJeY GdMb aj GJNGP GdELQGAGJ GddGReI bHd eQJcHgG, hjchf Yf WQjb GdOYhi GdLfGFjI GdJj JHGTQgG GdOhdI Yf WQjb GdfjGHI GdYGeI, MjK JJNP eLehYI ef GdELQGAGJ jWdb YdjgG GdELQGAGJ GdLfGFjI, hYdjg aEf bGfhf GdELQGAGJ GdLfGFjI (B"(3gh eLehYI GdbhGYO GdbGfhfjI GdJj JJVef ELQGAGJ GdHMK Yf GdLQGFe hVHWgG hhSGFd EKHGJgG, hJMOO GdSdWGJ GdeNJUI HedGMbI GdeLQe heMGceJg, hJHjf ELQGAGJ GdeMGce hJfajP GdCMcGe GdLfGFjI(B". (3hjJVM ef NdGd gPG GdJYQja, Cf bGfhf GdELQGAGJ GdLfGFjI jfXe GdOYhi GdLfGFjI efP dMXI JMQjcgG hMJi GfbVGFgG HMce HGJ, hGdeQGMd GdJj JeQ HgG GdOYhi GdLfGFjI,HOGjI ef eQMdI GdJMbjb GdGHJOGFj MJi eQMdI GdeMGceI hcPdc WQb GdWYf hGdgjFGJ GdeNJUI HeHGTQJgG hGdMce ajgG(B.s
(3CWQhMI (B((3OcJhGQg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdLfGFj, (B2021s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B360-375s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3bGfhf GdYbhHGJs; (3GeQ GdGMGdIs; (3GeQ GdMaXs; (3eMceI GdLfM hGdeNGdaGJ s; (3GdGMGdI Gdj eMceI GdLfGjGJs; (3bVGA GdGMGdIs; (3eMceI GdGMOGKs; (3GdeMGce GdGbJUGOjIs; (3GdbVGA GdYScQjs; (3GdWYf aj GeQ GdGMGdIs; (3Mb GdGSJFfGb s; (3GdWYf HGdfbV aj GeQ GdGMGdIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs